KEMAMPUAN MENULIS TEKS BIOGRAFI SISWA KELAS X SMA NEGERI 1 SELAKAU KABUPATEN SAMBAS - Lilian Widyasari; Martono Martono; Syambasril Syambasril (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractWriting is the ability to express ideas and thoughts in spoken form. Writing is an important component that learned in Indonesia subject. One of writing ability that learned in ten grade senior high school level is biography text. Writing a biography text could help students to always try and practice to improving comprehension and ability of students. In this regard, this research was focused on analyzed the students’ ability in writing biography text. The method used in this research is a descriptive method in quantitative study form. The technique used in this research to gain the participants is random sampling. The sample is 33 students in ten grade at SMA Negeri 1 Selakau. Test is used in this research to collect the data. The sample is 33 students in ten grade at SMA Negeri 1 Selakau. Based on the result, it can be concluded that the students’ ability in writing biography text based on all aspect in competent category with a percentage 82,42%. Based on analysisresult that have been done, the researcher making several suggestions. The teacher should give more attentions on the students’ ability in writing biography text.Keywords : Ability, biography text, writing.